Environmental Conservation Paradigm in islamic Ecological Perspective - Najib, Moh. (International Journal of Psychosocial Rehabilitation, 2020)
The occurrence of an environmental crisis is not just a matter of ecological damage alone, but also a moral and spiritual problem. To overcome this crisis, it must be reviewed comprehensively both ecologically and spiritually. Islam as eternal teaching must be explored so that it becomes a practical guide for Muslims around the world. However, Islamic teachings on the environment cannot be explored effectively without special tools such as theology, Sufism and Usul al-Fiqh. This paper will discuss the role of the Islamic ecology paradigm which includes the approach of ecology, Sufism and eco-usul al-fiqh for environmental conservation.